1994
DOI: 10.1002/mpo.2950230607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CPT‐11 (a unique DNA topoisomerase I inhibitor) on a highly malignant xeno‐transplanted neuroblastoma

Abstract: Although many advances have been made in the management of neuroblastoma, the prognosis of patients with advanced neuroblastoma remains poor, and constant efforts are being made to search for newer effective drugs. CPT-11 is a newly developed derivative of camptothecin and shows a unique anti-tumor activity by inhibiting DNA topoisomerase I. In this study the effects of CPT-11 on a human neuroblastoma xenograft, TNB9, were investigated according to the standard Battelle Columbus Laboratories protocol. TNB9 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…CPT-1 1 is clearly active against neuroblastoma and pPNET xenografts, as its anti-tumour activity was retained at doses lower than the optimal dosage. These results are in good agreement with those of Komuro et al (1994) who showed that CPT-11, administered i.p., induced significant tumour growth inhibition in the TNB9 neuroblastoma xenograft model, although no complete tumour regression was reported. CPT-11 was also found to be active against other paediatric cancer (Vassal et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…CPT-1 1 is clearly active against neuroblastoma and pPNET xenografts, as its anti-tumour activity was retained at doses lower than the optimal dosage. These results are in good agreement with those of Komuro et al (1994) who showed that CPT-11, administered i.p., induced significant tumour growth inhibition in the TNB9 neuroblastoma xenograft model, although no complete tumour regression was reported. CPT-11 was also found to be active against other paediatric cancer (Vassal et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…CPT-11 a semisynthetic water-soluble analog of camptothecin, is a DNA-topoisomerase I inhibitor and has demonstrated antitumor activity against a wide spectrum of both adult and pediatric xenografts in preclinical studies (Komuro et al, 1994;Vassal et al, 1996;Thompson et al, 1997a). We have previously shown that intravenous (i.v) treatment with CPT-11 resulted in extensive tumor regression and growth delay in three different NB xenograft models (Vassal et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…First, they have impressive activity against NB cell lines resistant to standard anti-NB agents (1)(2)(3)(4)(5); this finding implies that they may provide a novel non-cross-resistant chemotherapeutic addition to the standard drug armamentarium for NB. Second, their nonhematological toxicity (mucositis/topotecan, Refs.…”
Section: Introductionmentioning
confidence: 99%